Green Strategies of Powdery Mildew Control in Hop: From Organic Products to Nanoscale Carriers - Alejandra J. Porteous-Álvarez; M. Mercedes Maldonado-González; Sara Mayo-Prieto; Alicia Lorenzana; Ana I. Paniagua-García; Pedro A. Casquero (Journal of Fungi, 2021)
Humulus lupulus L. is a long-lived, perennial, herbaceous, and dioecious climbing plant. The foremost producers in the European Union are Germany, the Czech Republic, Poland, Slovenia, and Spain. The Spanish cultivated area is concentrated in the province of León. Powdery mildew, caused by Podosphaera macularis, menaces hop production and quality in all hop growing regions located in the Northern hemisphere, colonizing leaves, petioles, inflorescences, and finally cones. In this work, powdery mildew control was monitored, comparing nine fungicide strategies: five organics, two integrated disease management (IDM)-based, with and without Nutragreen® nanoscale carrier, and two conventional treatments (CON) with and without Nutragreen® nanoscale carrier. The organic treatments were able to diminish P. macularis on leaves, but no effect was observed in cones. CON treatments reduced the infection on leaves and cones and increased the cone quantity and quality. Likewise, IDM-based treatments provided satisfactory results as they diminished powdery mildew on leaves and cones. Finally, dose reduction using a Nutragreen® nanoscale carrier showed beneficial effects in the control of powdery mildew compared to the commercial dose. Hence, the use of nanoscale carries permits a 30% reduction in pesticide dose, which optimizes yield and hop quality, reduces risks linked to pesticides, and aids in compliance with public and international policy demands.